Investigating Work Engagement at the Workplace - Abidin, Nur Sherina Zainal; Adam, Shahira; Jah, Nurain Jantan Anua; Rahmat, Noor Hanim; Aziz, Afiqah Abd; Nadri, Hana Nadia (International Journal of Asian Social Science, 2021)
In order to be happy at the workplace, employees need to feel engaged with the work environment. Work engagement refers to a work-related mental state that is positive and fulfilling, characterized by vigor (high levels of energy while working), dedication (sense of meaning, enthusiasm, inspiration, pride and challenge) and absorption (the individual’s complete concentration at work, which makes time fly quickly without his noticing). Besides that, the personal energy that individuals bring to their work is associated with work engagement. This study is done to investigate the factors that allow work engagement at the workplace emphasizing in assisting and addressing experience gaps in the strictest sense of the word by assigning values for the lasting connections actions to the relevant individuals, causing the person or the team to simply focus on producing outcomes in a healthy workplace and collaborative nature.115 participants responded to a survey given online. Findings reveal several factors that can lead to a positive culture at the workplace.